Women, culture, and green transformation: A gendered participatory communication model for wellness tourism (BIS Humanities and Social Science, 2026)
Wellness tourism is increasingly promoted as a pathway to green transformation, yet its development in culturally rich communities raises ethical concerns regarding sacred traditions, gendered power relations, and community participation. This study examines how gendered communication practices and cultural sacredness shape wellness tourism development in Madura, Indonesia. Using a mixed-methods approach, data were collected through surveys with 286 respondents, focus group discussions, and in-depth interviews in selected village clusters in Sumenep and Pamekasan. Quantitative data were analyzed descriptively, while qualitative data were examined thematically. The findings show that Madurese women play a central role in preserving indigenous wellness knowledge, including jamu, ritual healing, and family-based care, but remain marginal in formal tourism planning. Communities also negotiate boundaries between practices that can be adapted for tourism and those that must be protected due to their sacred value. Participation is further limited by centralized governance and the gap between global wellness tourism discourse and local cultural meanings. Based on these findings, this study proposes the Gendered-Cultural Participatory Communication Model (G-CPM), consisting of five components: sacred knowledge protection, gendered agency negotiation, community curation, local-language meaning-making, and sustainability framing. This model reframes green transformation as a communicative and ethical process, contributing to participatory communication, gender studies, and sustainable tourism scholarship.